A comparison of isokinetic rotator cuff performance in wheelchair basketball athletes vs. non-athletes with spinal cord injury. (4th July 2021) - Freitas, Poliane Silva; Santana, Tiago Silva; Manoel, Lucas Sartori; Serenza, Felipe de Souza; Riberto, Marcelo
Abstract : Objectives: This study aimed to compare the isokinetic peak torque and, secondarily, other parameters of the rotator cuff in the shoulders of paraplegic wheelchair basketball athletes and non-athletes controls. Design: Cross-sectional study. Methods: Thirty-six complete spinal cord injured individuals aged between 18 and 45 years performed an isokinetic evaluation of peak torque, power, and work exerted by the rotator cuff muscle group, in a Biodex System. All Concentric isokinetic tests were performed in the seated position with the shoulder at a 45° abduction from the scapular plane and flexed at 30° to the frontal plane. Subjects completed five repetitions at 60°/s and 180°/s, and ten repetitions at 300°/s, bilaterally, with an interval of one minute between each series. Statistical analysis (t-test, P < 0.05) compared athletes and non-athletes, dominant and non-dominant upper limbs according to all isokinetic parameters and angular velocities. Results: Peak torque/weight, work, and muscle power of wheelchair basketball athletes were significantly greater than those of the control group (P < 0.05), but there were no statistical differences between dominant and non-dominant upper limb. Internal rotators were stronger than the external rotators both for athletes and for non-athletes. There is a positive correlation between peak torque and time since injury. Conclusions: Wheelchair basketball athletes showed greater peak torque and other muscle performance parameters, which suggest that wheelchair basketball influences the shoulder musculature of those with traumatic spinal cord injury.